Packaging of optical diffraction strain sensor - Duan, Lin. (2008)
The aim of this project is to package this Optical Diffraction Strain Sensor (ODSS) into a commercial prototype, intended for using in both laboratory and industrial settings. Following this packaging and testing, the system can be explored for applications in other domains of precision metrology, microelectronics, micro mechanics and mechanics of advanced materials etc.